2019
DOI: 10.3201/eid2505.180914
|View full text |Cite
|
Sign up to set email alerts
|

Management of Central Nervous System Infections, Vientiane, Laos, 2003–2011

Abstract: During 2003–2011, we recruited 1,065 patients of all ages admitted to Mahosot Hospital (Vientiane, Laos) with suspected central nervous system (CNS) infection. Etiologies were laboratory confirmed for 42.3% of patients, who mostly had infections with emerging pathogens: viruses in 16.2% (mainly Japanese encephalitis virus [8.8%]); bacteria in 16.4% (including Orientia tsutsugamushi [2.9%], Leptospira spp. [2.3%], and Rickettsia spp. [2.3%]); … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 46 publications
0
49
0
Order By: Relevance
“…The first report of acute JEV infection in Laos was by Moore et al, 7 through detection of anti-JEV IgM in cerebrospinal fluid (CSF) among patients with suspected central nervous system (CNS) infections at Mahosot Hospital, Vientiane. Recent studies have confirmed JEV infection across Laos, [8][9][10] more commonly in the north than in the south. Aubry et al 11 described JEV genotype 1 from the CSF of a patient from Vientiane Province.…”
Section: Introductionmentioning
confidence: 97%
“…The first report of acute JEV infection in Laos was by Moore et al, 7 through detection of anti-JEV IgM in cerebrospinal fluid (CSF) among patients with suspected central nervous system (CNS) infections at Mahosot Hospital, Vientiane. Recent studies have confirmed JEV infection across Laos, [8][9][10] more commonly in the north than in the south. Aubry et al 11 described JEV genotype 1 from the CSF of a patient from Vientiane Province.…”
Section: Introductionmentioning
confidence: 97%
“…Neurological manifestations and sequelae of scrub typhus and SFR have been overlooked. Numerous reports indicate that both Orientia and Rickettsia are significant causes of encephalitis and meningitis in the Asia-Pacific region [ 10 13 ]. O .…”
Section: Introductionmentioning
confidence: 99%
“…O . tsutsugamushi accounts for 17.9% of all bacterial central nervous system (CNS) infections in Laos and up to 25% of all encephalitic infections in India [ 10 , 13 ]. Rickettsia spp .…”
Section: Introductionmentioning
confidence: 99%
“…Central nervous system (CNS) infections cause significant mortality and morbidity worldwide, but especially in low- and middle-income countries (1). Common CNS infections include bacterial meningitis (BM), viral encephalitis, tuberculous meningitis (TBM) and cryptococcal meningitis (2), but there are >100 documented infectious causes of CNS infections (3). Additionally, over the last decade, antibody-mediated causes of encephalitis (e.g.…”
Section: Introductionmentioning
confidence: 99%